Homing of canine multipotent mesenchymal stromal cells after epidural transplant in a rabbit model of compressive spinal cord injury - Ramos, Mariana Cristina (2020)
Multipotent mesenchymal stromal cells (MSCs) have been presented by the scientific community is a promising alternative for the treatment of inflammatory, traumatic, vascular, and degenerative diseases of the central nervous system due to their anti-inflammatory, immunomodulatory, and neuroregenerative properties. One of the aspects that can affect the effectiveness of stem cell therapy is the transplantation route used. The aim of this study was to evaluate the homing of canine adipose derived MSCs (AdMSCs) transplanted via epidural injection in an experimental rabbit model of compressive spinal cord injury. New Zealand rabbits (n=8) were subjected to spinal cord injury induced by compression of the 10th thoracic segment. Immediately after the surgical procedure, the animals were subjected to the transplantation of marked AdMSCs with quantum dots through epidural injection between the L7–S1 spaces. Seven days after the transplant, the brain, spinal cord, lungs, kidney, spleen, and liver were collected and evaluated by bioluminescence imaging. The spinal cord segments L7–S1 and the thoracic injury site were evaluated by confocal microscopy to identify the presence of marked canine AdMSCs. Results showed that AdMSCs migrated to the thoracic spinal cord segment, lungs, brain, liver, and kidneys, and no bioluminescence was observed in the spleen. The presence of canine AdMSCs in the spinal cord indicates the capacity of these cells to overcome the dura mater and reach the transplantation site. Epidural delivery is feasible and minimally invasive and might be a good candidate for cell transplantation in the context of neurological diseases.